Estudio de pertinencia en la creación de la carrera de gastronomía para su aplicación en el Instituto Tecnológico Superior Cordillera como aporte a la soberanía alimentaria y al desarrollo de la matriz productiva del país - Mendoza Jaramillo, Friktzia Catherine (2018)
The present project focuses on determining the feasibility of the creation of the Gastronomy Career for the Technological Institute High Cordillera in order to develop its implementation in 2018. Once all the social, physical and economic scenarios required for its implementation have been applied, the viability of the proposal has been determined. It was possible to fulfill the objectives of the research aimed at presenting an innovative, fresh and applicable proposal considering the current environment, the supply and demand of professionals in the Gastronomic Area, in the same way an analysis of the institutions that offered similar with the purpose of identifying the competitive advantage of the Institution in relation to the rest and evidencing the alternatives of labor insertion, entrepreneurship and agreements with franchises that will be a labor alternative for the professional in this branch. Also always considering the importance of the technological training that forms professionals who know how to do things with capacity and the ability to lead and solve problems and conflicts in a timely and efficient manner. The demand for applicants and interested in training in Gastronomic Technology is growing more and more, which will allow the academic proposal submitted by ITSCO to have reasonable growth in the first 5 semesters. Undoubtedly Education in an inalienable right that forms human beings with the capacity to defend themselves in life, live it happily and with dignity, and for this fundamental objective is the Technological Institute High Cordillera.